2016
DOI: 10.1007/s00289-016-1727-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyurethane/POSS hybrid aqueous dispersions from mono-amino substituted POSS

Abstract: A series of linear polyurethane (PU) aqueous dispersions modified by polyhedral oligomeric silsesquioxane (POSS) was synthesized by incorporating various amounts (ca. 2-10 wt%) of a secondary amino-terminated monofunctional POSS in hexamethylene diisocyanate trimer (HDI-T), hexamethylene diisocyanate, poly(tetramethylene-oxide) and 2,2-bis(hydroxymethyl)propionic acid. Results from the gel permeation chromatography, Fourier-transform infrared spectroscopy, transmission electron microscopy, and X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Shot and cycle times vary, depending on the part size of filler and other components and the polyurethane system used. An average mold for an elastomeric part may be filled in one second or less and be ready for demolding in 30-60 s. Special extended gel-time polyurethane RIM systems allow the processor enough time to fill very large molds using equipment originally designed for smaller molds [61][62][63][66][67][68][69][70].…”
Section: Polyurethane/poss Nanocompositessynthesis and Processingmentioning
confidence: 99%
“…Shot and cycle times vary, depending on the part size of filler and other components and the polyurethane system used. An average mold for an elastomeric part may be filled in one second or less and be ready for demolding in 30-60 s. Special extended gel-time polyurethane RIM systems allow the processor enough time to fill very large molds using equipment originally designed for smaller molds [61][62][63][66][67][68][69][70].…”
Section: Polyurethane/poss Nanocompositessynthesis and Processingmentioning
confidence: 99%
“…And its active functional groups can improve the compatibility of the POSS with other matrix. Therefore it can be applied in polymers and improve its flame retardancy and smoke suppression 20,21 . Qu et al 22 modified graphene oxide with octa (propyl glycidyl ether) POSS and introduced it into epoxy resin (EP), and found that octa (propyl glycidyl ether) POSS could improve the dispersion of graphene oxide and enhance the flame retardancy of EP.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large attention paid to the effects induced by the presence of polyhedral oligomeric silsesquioxanes (POSSs), their stabilization activities were scarcely investigated. The influence of structured polymer materials [ 17 , 18 , 19 ], hybrid composition [ 20 , 21 , 22 ], preparation conditions [ 23 , 24 ] are the main directions that are envisaged by the majority of assays. Unfortunately, the contribution of POSS filler to the delay of oxidation in polymer materials was randomly reported [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%